Peran Sertifikat Hak Cipta dan Lisensi Dalam Menjamin Kepastian Hukum Pemegang Hak Cipta Atas Karyanya - Brian Jeremy Modami; R. Rahaditya (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Creation produced by the creator deserve proper legal protection. The use of copyrighted works by others can not be arbitrarily used without the creator’s and the holder of the copyright consent. This is because the creator can control what will be done to his creation and prevent the creation is used for harmful things. Creators can obtain permission to use their creations and strengthen their creations. One of the permissions that can be given to other parties is a license. Strengthening copyright protection can be done by obtaining a copyright certificate.